The influence of professional skepticism, time budget pressure, and materiality on audit quality (empirical study of public accounting firms in DKI Jakarta for the 2023 period) - Cynthia Belinda; Leonard Pangaribuan; Wiwin Prastio (Jurnal Scientia, 2024)
Audit quality is the result of an auditor's audit, which determines whether an audit is good or not. An audit conducted by an auditor can be considered of good quality if it meets the auditing standards. This study aims to provide empirical evidence of the effect of Professional Skepticism, Time Budget Pressure, and Materiality on Audit Quality. The research subjects were auditors working in public accounting firms in the DKI Jakarta region. Data collection was done by distributing questionnaires to 105 respondents. The sampling technique used was non-probability sampling with purposive sampling technique. The IBM SPSS Statistics 25 program was used to perform data analysis techniques, including classical assumption tests, coefficient of determination tests, F-tests, and t-tests. After testing, the research results showed that the statistical t-test for Professional Skepticism had a significance value of 0.000 (<0.05), Time Budget Pressure had a significance value of 0.399 (>0.05), and Materiality had a significance value of 0.000 (<0.05). Based on these results, it was proven that Professional Skepticism and Materiality have a positive and significant effect on audit quality. As for the Time Budget Pressure variable, it was not found to have a negative effect on audit quality.